DEVELOPMENT OF LEARNING MEDIA MATH SETS GAME BASED ON CONSTRUCT 2 WITH SCIENTIFIC APPROACH - Dewi Savitri; Sri Sulasteri; Nur Yuliany (International Conference on Social and Islamic Studies, 2021)
The purpose of this study is to find out the quality of Math Sets Game learning media that have been developed from the perspective of validity, practicality, and effectiveness in mathematics subjects. This research is a type of Research and Development research with the model used is ADDIE (Analysis, Design, Development, Application, and Evaluation). Students of class X SMK Negeri 6 Makassar are the subject of trials in this study. The instruments used are validation sheets, observation sheets, response questionnaires, and learning results tests. The results showed the resulting learning media was valid, practical, and effective, with the average validity of Math Sets Game learning media and research instruments being in the highly valid category with a score of 4.3. Practically, with an average percentage of learners' response questionnaires 86.8% and teacher response questionnaires are 84%. Effectively, the average percentage of learners' learning completion is 89%.